Introducing 3ds Max 2008 - Derakhshani, Dariush (Wiley Pub., 2008)
3ds Max is the power behind dynamic video games like Splinter Cell, Halo, and Gears of War. This book helps you work your way through the complexities of 3D modeling, texturing, animating, and visual effects. It includes explanations, tutorials, and hands-on projects to build your skills.